Falencias en los registros documentales y financieros y su incidencia en la validación de la información en la Distribuidora Farmacéutica Grupo Ronquillo Sandoya - Plazarte Martinez, Jaime Alfredo (2021)
For greater effectiveness in all the processes that correspond to their administration in the Grupo Sandoya Pharmaceutical Distributor, it must collect all its records in documents and like this, it is required that the financial records be duly kept, in this way you can exercise a validation of said data previously registered. The Grupo Sandoya Pharmaceutical Distributor performs these actions, but it has a drawback when it comes to controlling all the documents that this service entity uses, as well as the accounting documents, as there is no control, there are problems when trying to render accounts on activities that require the use of money, either for income or expenses, The best way to have control in all these documents on processes is to know how to have organization, discipline and have the materials and properly trained personnel to carry out these tasks that are of utmost importance for this entity. This investigation will be in charge of finding the shortcomings that are mainly responsible for the fact that the Pharmaceutical Distributor of Los Ríos is not adequately complying with the validation of its processes at the time of presenting them to the central, applying research tools focused on observation. field, respecting the restrictions due to current times.